Increased IgE serum levels are unrelated to allergic and parasitic diseases in patients with juvenile systemic lupus erythematosus - Bernadete L. Liphaus (Clinics, 2012)
OBJECTIVE: The aim of this study was to assess the IgE serum levels in juvenile systemic lupus erythematosus patients and to evaluate possible associations with clinical and laboratory features, disease activity and tissue damage. METHODS: The IgE serum concentrations in 69 consecutive juvenile systemic lupus erythematosus patients were determined by nephelometry. IgG, IgM and IgA concentrations were measured by immunoturbidimetry. All patients were negative for intestinal parasites. Statistical analysis methods included the Mann-Whitney, chi-square and Fisher's exact tests, as well as the Spearman rank correlation coefficient. RESULTS: Increased IgE concentrations above 100 IU/mL were observed in 31/69 (45%) juvenile systemic lupus erythematosus patients. The mean IgE concentration was 442.0 ± 163.4 IU/ml (range 3.5-9936.0 IU/ml). Fifteen of the 69 patients had atopic disease, nine patients had severe sepsis and 56 patients presented with nephritis. The mean IgE level in 54 juvenile systemic lupus erythematosus patients without atopic manifestations was 271.6 ± 699.5 IU/ml, and only nine of the 31 (29%) patients with high IgE levels had atopic disease. The IgE levels did not statistically differ with respect to the presence of atopic disease, severe sepsis, nephritis, disease activity, or tissue damage. Interestingly, IgE concentrations were inversely correlated with C4 levels (r = -0.25, p = 0.03) and with the SLICC/ACR-DI score (r = -0.34, p = 0.005). The IgE concentration was also found to be directly correlated with IgA levels (r = 0.52, p = 0.03). CONCLUSIONS: The present study demonstrated for the first time that juvenile systemic lupus erythematosus patients have increased IgE serum levels. This increase in IgE levels was not related to allergic or parasitic diseases. Our results are in line with the hypothesis that high IgE levels can be considered a marker of immune dysregulation.